MULITPLE IMAGE SUPER RESOLUTION BY USING PYTHON - Narendra, P. Lakshmi; Ganapathy, Kirupa (International Journal of Psychosocial Rehabilitation, 2020)
To construct the high resolution image in this paper used the single image super resolution. For the accuracy and the efficiency the deep convolution network is implied. The MSSRD technique is used for the fast construction of the single image super resolution. In this paper the transformation of the low resolution image to high resolution image is proposed. It also concentrates in the deep network architecture. However the existing method focuses in the shallow network layer or stack layers. The reduction in the number of parameters is made by the convolution blocks. The noise is get reduced to the maximum level and the SSIM with reduced number of parameters.